Straightforward preparation of fluorinated covalent triazine frameworks with significantly enhanced carbon dioxide and hydrogen adsorption capacities. Issue 47 (22nd November 2019) - Wang, Guangbo; Onyshchenko, Yuliia; De Geyter, Nathalie; Morent, Rino; Leus, Karen; Van Der Voort, Pascal
Abstract : Herein, we report the construction of a set of fluorinated microporous covalent triazine frameworks (FCTFs) with appropriate CO2 -philic functionalities (N and F) and high porosities for effective gas adsorption and separation. Abstract : The development of advanced functional porous materials for efficient carbon capture and separation is of prime importance with respect to energy and environmental sustainability and employing covalent triazine frameworks as the adsorbents for carbon capture is deemed to be one of the most promising means to alleviate this issue. Herein, we report the construction of a set of partially fluorinated microporous covalent triazine frameworks (FCTFs) with appropriate CO2 -philic functionalities (N and F) and high porosities (up to 2060 m 2 g −1 ) for effective gas adsorption and separation. Markedly, the CO2 adsorption capacity of the FCTF materials prepared at a ZnCl2 /monomer ratio of 20 and 400 °C reaches up to 4.70 mmol g −1 at 273 K and 1 bar, which is among the top level of all the reported CTFs. In addition, the studied FCTFs also exhibit a significantly high H2 uptake of 1.88 wt% at 77 K and 1 bar, outperforming most of the reported CTF materials under identical conditions. Apart from this, the obtained FCTF materials also display moderate CO2 selectivities over N2 (28) and CH4 (5.6) at room temperature.